The Application and Challenges of Brain Organoids in Exploring the Mechanism of Arbovirus Infection - Baoqiu Cui; Zhijie Wang; Anum Farid; Zeyu Wang; Kaiyue Wei; Naixia Ren; Fengtang Yang; Hong Liu (Microorganisms, 2025)
Arboviruses, transmitted by blood-sucking arthropods, are responsible for significant human and animal diseases, including fever, hemorrhagic fever, and encephalitis, posing a serious threat to global public health. Nevertheless, research on the mechanisms of arbovirus infection and the development of therapeutic interventions has been impeded. This delay is primarily due to the limitations inherent in current in vitro research models, including cell cultures and animal models. The simplicity of cell types and interspecies differences present significant obstacles to advancing our understanding of arbovirus infection mechanisms and the development of effective drugs. Human brain organoids, derived from human pluripotent stem cells or human embryonic stem cells and cultured in three-dimensional systems, more accurately replicate the extensive neuronal cellular diversity and key characteristics of human neurodevelopment. These organoids serve as an ideal model for investigating the intricate interactions between viruses and human hosts, and providing a novel platform for the development of antiviral drugs. In this review, we summarize how brain organoid models complement classical approaches to accelerate research into the infection mechanisms of arboviruses, with a particular focus on the types of neural cells, key factors, and cellular signaling pathways involved in the arbovirus infection of brain organoids that have been reported. Furthermore, we examine the development of brain organoids, address their current limitations, and propose future directions to enhance the application of brain organoids in the study of arboviral infectious diseases.